Examining career shadowing in genetic counseling: Perspectives of shadowees, program directors, and genetic counselors. Issue 5 (31st March 2021) - Agre, Katherine; Essendrup, Anna; Koellner, Christine; Rust, Laura; Deyle, David
Abstract: Career shadowing can be a valuable opportunity for individuals to experience the daily activities of a working professional. However, there is no published research regarding the impact of shadowing for individuals hoping to pursue a career as a genetic counselor (GC) (termed 'shadowees'). Additionally, little is known about the impact of shadowing on practicing GCs, nor the value of shadowing in the application and admission process for genetic counseling graduate programs. For this study, three independent surveys were developed and sent to three stakeholder groups: shadowees in the Minnesota Genetic Counseling Experience Program, program directors within the Association of Genetic Counseling Program Directors, and members of the National Society of Genetic Counselors. Quantitative and qualitative analyses were performed on responses. The survey of shadowees ( n  = 55) found that the majority believed that shadowing had either a 'very' or 'somewhat positive' impact on their decision to become a GC and on their application to a genetic counseling graduate program (81.8% and 91.3%, respectively). Of the participating program director respondents ( n  = 43), the majority indicated that having shadowing experience was either 'moderately' or 'extremely important' in offering an interview or for acceptance into a graduate program (63% and 56%, respectively). While programs differ in evaluation of shadowing experiences, most program directors indicated that an applicant's ability to speak to their shadowing experience was the most important factor in admissions consideration (71%). Among the GCs surveyed ( n  = 325), 69.2% have hosted shadowees; of these, 82.7% indicated that hosting a shadowee decreases their efficiency at work. Despite this drawback, the majority of respondents expressed a willingness and motivation to host shadowees to help the shadowee (64.8%) and to promote the genetic counseling profession (32.6%). These findings suggest the need for additional research and the development of resources for GCs to increase access of career shadowing. Abstract :